2003
DOI: 10.1103/physrevb.67.144415
|View full text |Cite
|
Sign up to set email alerts
|

Theory of dopants and defects in Co-dopedTiO2anatase

Abstract: We report first-principles microscopic calculations of the formation energy, electrical activity, and magnetic moment of Co dopants and a variety of native defects in TiO2 anatase. Using these results, we use equilibrium thermodynamics to predict the resulting carrier concentration, the average magnetic moment per Co, and the dominant oxidation state of Co. The predicted values are in good agreement with experiment under the assumption of O-poor growth conditions. In this regime, a substantial fraction of Co d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…In the LDA and GGA the single-particle state induced by V 0 O and V þ O is above the conduction-band minimum, so that these charge states cannot be stabilized [26,35,36], prohibiting drawing reliable conclusions about the relative energetic stability of the various charge states. In HSE, the neutral and positive charge states can be explicitly calculated and their energy compared with that of the 2þ charge state [26].…”
Section: þmentioning
confidence: 98%
“…In the LDA and GGA the single-particle state induced by V 0 O and V þ O is above the conduction-band minimum, so that these charge states cannot be stabilized [26,35,36], prohibiting drawing reliable conclusions about the relative energetic stability of the various charge states. In HSE, the neutral and positive charge states can be explicitly calculated and their energy compared with that of the 2þ charge state [26].…”
Section: þmentioning
confidence: 98%
“…Some experimental results [20,21] have revealed that co-doping TiO 2 could narrow its band gap, thereby increasing the efficiency of the photocatalysis in the visible range. Co-doped anatase, in particular, is an object of a very large number of publications and review papers [22][23][24][25][26][27][28][29]. Amadelli et al [30] synthesized cobalt-modified TiO 2 by the incipient impregnation method.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In memristor devices, TiO 2 has become a very important field-tunable layer in between metallic electrodes, where the insulating property of the film is overcome by field induced anionic defect dynamics. 8 In a Co-TiO 2 /TiO 2 /Co-TiO 2 spintronic heterostructure where the electrodes are ferromagnetic, the role of TiO 2 is a pure insulator.…”
Section: Introductionmentioning
confidence: 99%